Diversity of morphological characters and seed growth of (Amorphaluus muelleri) plants based on sources of planting materials and growth media. Issue 1 (January 2022) - Firdaus, N K; Pranowo, D; Herman, M; Listyati, D; Aunillah, A.
Abstract: Amorphaluus muelleri has been popular among farmers, with the high demand in the world market. However, the information and knowledge on the provision of seed sources, which is also one of the limiting factors in A. muelleri cultivation technology. This research aimed to identify and characterize the morphological diversity and growth response of A. muelleri plants in polybags with two treatments of growing media as seed sources. This research was conducted in Pakuwon experimental station, the IIBCRI, Sukabumi, from October 2020 – April 2021. The study was conducted in a factorial randomized block design with two factors; source of planting materials (seeds, bulbils, small tubers), and growing media, soil + organic manure (1:1), and soil+organic manure+husk charcoal (1:1:1). The results showed the variability of morphological characters in weight of 100 grains, shape of sources, stem height, age of fully open leaf plants, stem diameter, number of leaves, the emergence of second shoots, canopy diameter, and presence of bulbils. While the results on plant growth rates of the interaction between the factors only occurred on plant height, shoots number, and tuber weight. Planting material from bulbils and growing media with the addition of husk charcoal gave the best response to each variable.